Seed bank of seasonally flooded grassland: experimental simulation of flood and post-flood - Bao, Francielli [UNESP]; Elsey-Quirk, Tracy; de Assis, Marco Antonio [UNESP]; Pott, Arnildo (Springer Nature, 2018)
Wetland seed banks comprise the propagules of plant species that have species-specific germination requirements for germination in either flooded or dry conditions. At the community level, wetland structure and succession during and after a seasonal flooding event depends upon the early life-history requirements of species, including germination under flooded and dry conditions. We examined the effects of simulated flood and post-flood scenarios on seedling emergence from a seed bank of seasonally flooded grassland in the Pantanal, Brazil. Field samplings were conducted in both wet and dry seasons, both of which were subject to flood and post-flood conditions. A total of 70 species emerged from the seed bank, dominated by Poaceae and Cyperaceae. Sixteen species were exclusive to the wet and one exclusive to the dry season. The richness of perennial species was higher under flood conditions, while the richness of annuals was greater post-flood. In general, the aquatic and amphibious species exhibited a significant germination response to flooding. Terrestrial species only germinated in post-flood conditions, with higher richness in the dry season. Four species had high seedling abundance in both treatments. The capacity of regeneration by seeds is high in these grasslands and can be increased by seasonal flooding and drawdown. In these seasonally flooded grasslands, we observed three main germination strategies: under flooded conditions, aquatic and amphibious species; post-flood conditions, an explosion of annual amphibious and terrestrial species; and in moist soil, perennial terrestrial species. The differential responses to flooding versus post-flood conditions help to maintain the structure and species richness in the community over time.
Keywords: Growth forms; Life cycle; Seasonal flooding; Seedling; Wetland